In vitro evidence that 5-hydroxytryptamine increases efflux of glial glutamate via 5-HT(2A) receptor activation. - Meller, R; Harrison, P; Elliott, J; Sharp, T (2002)
Recent studies have established the presence of 5-hydroxytryptamine (5-HT)(2A) receptors on glial cells in culture and in the brain in situ. Here we used cultured C6 glioma cells to investigate the possibility that 5-HT(2A) receptors on glia regulate glutamate release from the cell. The efflux of endogenous glutamate from cultured C6 glioma cells was increased by addition of 5-HT in a concentration-dependent manner (maximal effect +200%). The efflux of serine and aspartate was not altered. The effect of 5-HT was mimicked by both the nonselective 5-HT receptor agonist quipazine and the selective 5-HT(2) receptor agonist 4-iodo-2,5-dimethoxyamphetamine (DOI; both 0.01-100 microM). The 5-HT(2A) receptor antagonists ketanserin (1 microM) and spiperone (1 microM) inhibited the glutamate response to 5-HT, quipazine, and DOI, whereas the effect of 5-HT was not inhibited by the 5-HT(2B/C) receptor antagonist SB200646 (1 microM). The effect of 5-HT on glutamate was specific in that it was reduced in low-calcium medium but was not prevented by furosemide (5 mM), which prevents cell swelling-induced glutamate release. Finally, the glutamate uptake inhibitor 2,4,trans-pyrollidine dicarboxylic acid (50 microM) did not block the 5-HT-induced efflux of glutamate, making involvement of glutamate transport unlikely. In conclusion, 5-HT stimulates the efflux of glutamate from C6 glioma cells following 5-HT(2A) receptor activation and involves a calcium-dependent mechanism.